Glasgian Novel in Work of Alasdair Gray - E. A. Martynenko (Научный диалог)
The representation of the urban space in the prose of the major Scottish writer A. Gray on the material of his key novels “Lanark” (1981), 1982, “Janine” (1982) and “Poor things” (1992) is analyzed in the article. It is noted that A. Gray made a significant contribution to the formation of the Glasgian novel, the specificity of which is defined more exactly in the works of M. Burgess and M. Gregorova. It is shown that, like other Glasgian writers, in his works A. Gray reflects on the consequences of the dehumanizing influence of the city on a person, however, in contrast to them, he makes a choice in favor of protagonists who are simultaneously representatives of the working and middle classes. The author note that in the novel “Lanark” the city is shown through the prism of three-time layers: a nostalgic past, a bleak present and an apocalyptic future. It is indicated that mortality becomes the thematic dominant, as a result of which Glasgow acquires the features of the underworld. It is proved that in A. Gray’s prose the Glasgian locus acts as a “place of memory”, while the motive of “recreating” memories from fragmentary facts of urban life plays a significant role in order to reconstruct the historical appearance of Glasgow or create fictitious memories of it in the reader.